2018
DOI: 10.1053/j.tcam.2018.08.005
|View full text |Cite
|
Sign up to set email alerts
|

Retrospective Biomolecular Investigation of Coxiella burnetii and Leptospira spp. DNA in Cases of Abortion, Stillbirth and Neonatal Mortality in Dogs and Cats

Abstract: A B S T R A C T Abortion and neonatal mortality are events that can occur in breeding bitches and queens. It has been reported that up to 55% and 33% of these cases remain without a known cause, respectively, in canine and feline pregnancies. Unusual abortigenic and potentially zoonotic agents, including Coxiella burnetii and Leptospira spp., may be involved in these cases. C. burnetii is able to cause reproductive disorders in cattle, sheep and goats, and cases of abortion have been observed in dogs and cats.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 30 publications
0
7
0
Order By: Relevance
“…Previous serological studies carried out in Italian dogs found different prevalences ranging from 0.87% to 8% [ 17 , 18 ], whereas a survey to detect C. burnetii in canine placenta and aborted fetuses did not find positive samples [ 20 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous serological studies carried out in Italian dogs found different prevalences ranging from 0.87% to 8% [ 17 , 18 ], whereas a survey to detect C. burnetii in canine placenta and aborted fetuses did not find positive samples [ 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…Even though the role of dogs in Q Fever epidemiology raises the interest of researchers in view of the One Health perspective, data about the spreading of this infection in canine populations are scant. In particular, investigations carried out in Italy were mainly performed on farm animals and wildlife [ 10 , 11 , 12 , 13 , 14 , 15 , 16 ], but studies on companion animals are very limited [ 17 , 18 , 19 , 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…Leptospirosis is reported worldwide, and cases of feline leptospirosis have been described in Africa (Algeria and Reunion Island) [ 4 , 5 , 6 ], Asia (Iran, Japan, Malaysia, Taiwan and Thailand) [ 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 ], America (Brazil, Chile, Canada, Mexico, the Caribbean island of Saint Kitts and the USA) [ 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 ], Europe (the Czech Republic, Estonia, Germany, Greece, Serbia and Spain) [ 27 , 28 , 29 , 30 , 31 , 32 , 33 ], the United Kingdom (Scotland) [ 34 ], and Oceania (New Zealand and Australia) [ 35 , 36 , 37 ]. In Italy, Stefanetti and others [ 38 ] retrospectively investigated the role of Leptospira spp. in cases of abortion, stillbirth and neonatal mortality in cats, but none of the pathologic samples (placenta, pooled organs of fetuses and neonates) were found positive.…”
Section: Introductionmentioning
confidence: 99%
“…Although pig hunters are not recognised by human health authorities in Qld as being an at‐risk group for Q fever, their exposure to the environment and feral pigs, potential hunting of other wildlife species like macropods and interaction with dogs may be associated with an increased risk. Increasingly, species other than ruminants are being implicated as potential sources of infection including cats and dogs, both of which have been associated with human outbreaks of Q fever, usually linked with attendance at parturition 9, 10, 37–47 …”
Section: Figurementioning
confidence: 99%
“…Increasingly, species other than ruminants are being implicated as potential sources of infection including cats and dogs, both of which have been associated with human outbreaks of Q fever, usually linked with attendance at parturition. 9 , 10 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47…”
mentioning
confidence: 99%